2022
DOI: 10.3390/diagnostics12020352
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against 4 Atypical Post-Translational Protein Modifications in Patients with Rheumatoid Arthritis

Abstract: Patients with rheumatoid arthritis (RA) show autoantibodies against post-translational protein modifications (PTMs), such as anti-citrullinated protein antibodies. However, the range of recognized PTMs is unknown. Here, we addressed four PTMs: chlorination, non-enzymatic glycation, nitration, and homocysteinylation, identified as targets of atypical RA autoantibodies in studies whose protocols we have followed. The modified antigens included collagen type II, an extract of synovial proteins and a selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(198 reference statements)
0
7
0
Order By: Relevance
“…Antibody responses against COL2 modified by hypochlorous acid were evaluated in this study, together with antibodies against two other collagen oxidative modifications that can be present in inflamed RA joint—glycation and nitration. The obtained results led to the conclusion that antibodies targeting these PTMs are absent or inconsequential in RA patients [ 162 ].…”
Section: Collagen Type II (Col2) Posttranslational Modifications In R...mentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody responses against COL2 modified by hypochlorous acid were evaluated in this study, together with antibodies against two other collagen oxidative modifications that can be present in inflamed RA joint—glycation and nitration. The obtained results led to the conclusion that antibodies targeting these PTMs are absent or inconsequential in RA patients [ 162 ].…”
Section: Collagen Type II (Col2) Posttranslational Modifications In R...mentioning
confidence: 99%
“…These findings could be related to joint COL2 supported by the well-known anti-CarB immunity, while evidence indicating the existence of anti-glycated collagen in RA development are scarce, despite the fact that glycation was proven in RA despite the absence of hyperglycemia [ 166 ] and increased levels of advanced glycation end products were detected in the serum, synovial fluid and urine of RA patients [ 167 , 168 ]. A recent report by Rodriguez-Martinez et al showed evidence for the presence of antibodies specific to glycated COL2 in the sera of RA patients [ 162 ], but the magnitude of the detected signal was relatively small to conclude that immunity against this type of COL2 modification plays a significant role, suggesting a more restricted posttranslationally modified autoantigens repertoire in RA.…”
Section: Collagen Type II (Col2) Posttranslational Modifications In R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such modifications include both enzymatic (e.g., phosphorylation, methylation, and ubiquitination) and nonenzymatic (e.g., glycation, oxidation/reduction, and acetylation) changes [ 16 ]. Several post-translationally modified proteins have already been identified as autoantigens in the RA sera [ 17 ]. For example, autoantibodies to post-translationally carbamylated or acetylated proteins have been discovered in the RA [ 17 , 18 , 19 , 20 ].…”
Section: Glucose May Enhance Autoimmune Responses Via Antigen Modific...mentioning
confidence: 99%
“…Several post-translationally modified proteins have already been identified as autoantigens in the RA sera [ 17 ]. For example, autoantibodies to post-translationally carbamylated or acetylated proteins have been discovered in the RA [ 17 , 18 , 19 , 20 ]. The citrullinated proteins are the representative example of such modified proteins because the antibodies against the citrullinated proteins (anticitrullinated protein antibodies or ACPA) are a well-established hallmark of RA diagnosis and disease assessment [ 18 ].…”
Section: Glucose May Enhance Autoimmune Responses Via Antigen Modific...mentioning
confidence: 99%